The Development of Learning Materials for Multicultural-Based Civic Education to Improve Students’ Learning Achievements - Kurniawan Kurniawan; Wachidi Wachidi; Turdjai Turdjai; Wasidi Wasidi (Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Kerinci, 2021)
The research objective is to produce learning materials for multicultural-based Civic Education to improve students’ learning achievements. The development of this learning material applies the ADDIE model. The subjects of this study were four experts as validators, and at the evaluation stage, a quasi-experiment was carried out with a sample of 90 students. The population of quasi-experiment is students of Teacher Education of Elementary School Study Program of State Islamic Institute of (IAIN) Curup. The sample was selected through a purposive technique. The research instruments are validation sheets, practicality sheets, and achievement tests. The achievement test data were analyzed using covariate analysis (ANCOVA). The data analysis results state that multicultural-based Civic Education learning materials have met a high level of validity based on expert reviews and empirical tests. It has also met a high level of practicality. The multicultural-based Civic Education learning materials have met a high level of effectiveness, and the learning achievements of students who are taught with these learning materials are better than the learning achievements of students who are taught conventionally.